2014
DOI: 10.1186/1471-2229-14-83
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes for drought tolerance by whole-genome resequencing in maize

Abstract: BackgroundDrought stress is one of the major limiting factors for maize production. With the availability of maize B73 reference genome and whole-genome resequencing of 15 maize inbreds, common variants (CV) and clustering analyses were applied to identify non-synonymous SNPs (nsSNPs) and corresponding candidate genes for drought tolerance.ResultsA total of 524 nsSNPs that were associated with 271 candidate genes involved in plant hormone regulation, carbohydrate and sugar metabolism, signaling molecules regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 78 publications
2
81
0
3
Order By: Relevance
“…Transcriptome analysis of the wild rice Oryza rufipogon has led to the identification of 37 drought response genes differentially expressed in roots on application of drought stress (Tian et al, 2015). A transcription factor HYR which is associated with photosynthetic carbon metabolism has been identified, and its expression in rice has led to enhanced photosynthesis under drought and other environmental stresses, and resulted in increased yield under stress (Ambavaram et al, 2014 (Xu et al, 2014). Similar approaches in rice can be used to identify candidate genes responsible for drought tolerance, subsequently to be used in crop improvement programmes.…”
Section: Prospects For Increasing Drought Tolerance In Ricementioning
confidence: 99%
“…Transcriptome analysis of the wild rice Oryza rufipogon has led to the identification of 37 drought response genes differentially expressed in roots on application of drought stress (Tian et al, 2015). A transcription factor HYR which is associated with photosynthetic carbon metabolism has been identified, and its expression in rice has led to enhanced photosynthesis under drought and other environmental stresses, and resulted in increased yield under stress (Ambavaram et al, 2014 (Xu et al, 2014). Similar approaches in rice can be used to identify candidate genes responsible for drought tolerance, subsequently to be used in crop improvement programmes.…”
Section: Prospects For Increasing Drought Tolerance In Ricementioning
confidence: 99%
“…In recent years, molecular mechanisms for tolerance to drought stress in plants have become an active area of investigation and many genes regulated by drought stress have been reported in a variety of plants (Sehgal et al, 2012;Thudi et al, 2014;Xu et al, 2014). Very little is known about the physiological and molecular mechanisms by which the model legume M. truncatula responds to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2014) have identified more than 10,000,000 SNP loci from 801 re-sequenced rice varieties. Xu et al (2014) have found a total of 6,385,011 SNPs through re-sequencing 15 maize inbreds and compared them to maize B73 reference genome. Another study yielded a total of 4,290,679 unique SNPs from eight tomato lines when each genome was separately compared to the reference genome (Causse et al 2013).…”
Section: Molecular Marker Discoverymentioning
confidence: 99%
“…Loss of this gene (DST) function will enhance stomatal closure and decrease stomatal density, resulting in improved drought and salt tolerance in rice (Huang et al 2009b). Similarly, after the genome sequence of maize became available, candidate genes were identified for drought tolerance so that they could be used for the development of drought tolerance varieties (Xu et al 2014). In one study, more than 6,000 SNPs were found in drought stress related genes from two contrasting cultivars of Soybean: sensitive (BR 16) and tolerant (Embrapa 48).…”
Section: Abiotic and Biotic Stress Tolerance Variety Developmentmentioning
confidence: 99%
See 1 more Smart Citation